2022
DOI: 10.1177/08445621221118800
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Perceived Organizational Support of Nurses on Their Resilience: A Cross-Sectional Study From Turkey

Abstract: Background Throughout and following the ongoing Coronavirus outbreak, there is an urgent need to focus on organizational support strategies aimed at improving the resilience of nurses. Purpose This research aims to examine the relationship between the nurses’ perceived organizational support and their resilience levels, and to reveal the characteristics that make a significant difference. Methods The data of this descriptive and cross-sectional study were collected from 722 nurses in February 2021 using the we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…Our study verified the positive association between perceived organizational support and resilience among emergency nurses, but the direct effect level between the two was low in the mediation model. This is consistent with the conclusion of previous studies that nurses with higher levels of perceived organizational support also have higher levels of resilience, and perceived organizational support is an essential predictor of nurse resilience (Liu et al., 2020; Karadas et al., 2023). Organizations have a significant role in facilitating the development of resilience among healthcare workers, with support from organizations serving as a crucial environmental component in sustaining nurses' resilience (Cooper et al., 2020; Koh et al., 2020).…”
Section: Discussionsupporting
confidence: 92%
“…Our study verified the positive association between perceived organizational support and resilience among emergency nurses, but the direct effect level between the two was low in the mediation model. This is consistent with the conclusion of previous studies that nurses with higher levels of perceived organizational support also have higher levels of resilience, and perceived organizational support is an essential predictor of nurse resilience (Liu et al., 2020; Karadas et al., 2023). Organizations have a significant role in facilitating the development of resilience among healthcare workers, with support from organizations serving as a crucial environmental component in sustaining nurses' resilience (Cooper et al., 2020; Koh et al., 2020).…”
Section: Discussionsupporting
confidence: 92%
“…Also, Karadas et al. (2022) found a statistically significant relationship between perceived organizational support and psychological resilience in nurses working in pandemic clinics. Psychological resilience has a key moderating role in mitigating the psychological impact of nurses in the face of the COVID‐19 pandemic (Sierra‐García et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Labrague and De Los Santos (2020) conducted a study on 325 nurses and determined that those with high organizational support had lower levels of anxiety associated with COVID-19. Also,Karadas et al (2022) found a statistically significant relationship between perceived organizational support and psychological resilience in nurses working in pandemic clinics. Psychological resilience has a key moderating role in mitigating the psychological impact of nurses in the face of the COVID-19 pandemic(Sierra- García et al, 2022).…”
mentioning
confidence: 83%
“…26 One study conducted with nurses working in internal medicine, surgery and intensive care units showed that the highest level of moral distress was experienced due to treatments that were not expected to benefit patients, aggressive care, and the competence of healthcare providers. 25 Oh and Gastmans stated that institutional factors such as working environment, number of staff, and communication affect the moral distress experienced by nurses. 32 In the "Ethical Codes for Nurses" guide revised by the International Council of Nurses (ICN) in 2021, it is stated that nurses' colleagues and other healthcare professionals take appropriate measures to protect patients when the patient is in danger due to institutional policies, practices or misuse of technology.…”
Section: Discussionmentioning
confidence: 99%
“…The form consists of 11 questions that aim to collect information about the following characteristics of nurses: age, gender, marital status, education level, the unit where the nurse is working, work shifts, years of experience in the clinic, hospital, and profession, encountering ethical problems at work, and intention to quit the job. 25,26 Perceived Organizational Support Scale: The scale is developed by Giray and Şahin. 27 The Perceived Organizational Support Scale consists of 12 items.…”
Section: Personal Information Formmentioning
confidence: 99%